Vascular Endothelial Growth Factor Receptor, fms-Like Tyrosine Kinase-1 (Flt-1), as a Novel Binding Partner for SARS-CoV-2 Spike Receptor-Binding Domain - Mutahar, Adel Zaid I.; Devaramani, Manjunath; Dayal, Renu; Saini, Dinesh Kumar; Salimath, Paramahans V.; Salimath, Bharathi P. (Frontiers in Immunology, 2022)
Angiotensin converting enzyme 2 (ACE-2) and neuropilin 1, a vascular endothelial growth factor (VEGF) receptor, were identified to bind to SARS-CoV-2 spike receptor-binding domain (spike RBD). In silico analysis based on 3D-structure, multiple sequence alignment, and molecular docking of second domain of soluble Flt-1 (sFlt-1) and spike RBD revealed structural similarities, sequence homology, and protein-protein interaction. Interaction and binding of recombinant spike RBD (rspike RBD) and recombinant sFlt-1 (rsFlt-1) in vitro induced a conformational change, as revealed by spectrofluorimetric data, with increased fluorescence intensity in emission spectra as compared to either of the proteins alone. Results on ELISA confirmed the binding and cross-reactivity of rspike-RBD and rsFlt-1 as determined by using either specific antibodies towards each protein or immunized human serum. We found that polyclonal or monoclonal anti-spike RBD antibodies can recognize either rsFlt-1 or rspike RBD, showing cross-reactivity for the two proteins in a dose-dependent binding response. Recognition of bound rspike RBD or rsFlt-1 by anti-Flt-1 or anti-spike RBD antibodies, respectively, as observed by immunoblotting further confirmed the interaction between the two proteins. Identification of rspike RBD binding to Flt-1 receptor on A549 cells was demonstrated by immunoprecipitation and immunoblot analysis. Further, The binding of rspike RBD to Flt-1 receptor was shown using immunofluorescence on 2D-culture or 3D-spheroid of MDA-MB-231 cells which over-express Flt-1 receptor. Together, our study concludes that Flt-1 receptor is a novel binding partner for SARS-CoV-2 spike RBD.